Contactless palmprint alignment based on intrinsic local affine-invariant feature points - Phromsuthirak, Choopol; Tangsuksant, Watcharin; Sanpanich, Arthorn; Pintavirooj, Chuchart (My University, 2014)
A Palmprint, biométrie characteristics, was mostly found in civil and commercial applications for security system because it has more reliable and easy to capture by low resolution devices. This paper was to develop a new contactless palmprint alignment with general USB camera on tripod. The palmprint image is acquired by this camera and using intrinsic local affine-invariant key points residing on the area patches spanning between two successive fingers to align palmprint image. The key points are relative affine invariant to affine transformations so this algorithm does not need the guidance pegs in acquisition process to fix hand position to avoid the scaling, translation and rotation problems for correctly palmprint image alignment. Finally, the developed algorithm was tested by 10 left-handed palmprint images collected from different subjects. The simulation results indicate by distance map error of 1.4899 pixels.
Keywords: Biometric; Convex hull; Otsu's thresholding; Palmprint alignment; Palmprint identification